MODEL MANAJEMEN STRATEGIK BERBASIS PEMIKIRAN ISLAM: STUDI PADA PONDOK PESANTREN LPI AL-HAMIDY PP BANYUANYAR - Kholilur Rahman (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to describe the implementation of Islamic thought in strategic management and to formulate a strategic management model based on Islamic values at Pesantren Al-Hamidy Banyuanyar. This research employs a descriptive qualitative approach, using in-depth interviews, observations, and documentation as data collection techniques. The research informants include the pesantren caregivers, institutional leaders, teachers (asatidz), and managers of educational units. Data analysis follows the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings show that the application of strategic management at Pesantren Al-Hamidy is grounded in Islamic principles such as shūra, amanah, itqan, and maqasid al-shari‘ah. The strategic planning process is carried out through structured deliberation, strengthening of the vision and mission, and determining program priorities based on the needs of students and the community. At the implementation stage, the values of amanah and discipline serve as the main foundation for human resource management and program execution. Strategy evaluation is conducted periodically through weekly deliberation forums and quarterly evaluation meetings. This study produces a strategic management model grounded in Islamic thought consisting of four main components: Islamic value foundation, strategy formulation, strategy implementation, and continuous evaluation. This model is expected to serve as a reference for Islamic educational institutions in developing effective and spiritually oriented strategic management